The lame man at the pool of Bethesda: Christological and doxological significance of characterisation in John 5 - Hahn, Nathan; van Eck, Ernest (In die skriflig : tydskrif van die Gereformeerde Teologiese Vereniging, 2021)
In any research of the biblical themes in Scriptures, the exegete must exercise discipline in strictly adhering to an exegetical process wherein the text is permitted to speak for itself in the context of the passage. This article therefore explored the literary traits and analysed characterisations in the story of the lame man at the pool of Bethesda as portrayed in John 5 through a 'narratological and exegetical' approach, considering literary, social, cultural and historical criticism with significant attention given to the text of the author or narrator. It is very important to know the author's theological viewpoint as seen in the characterisation of an anonymous character in the related gospel narrative, because it may be easily be overlooked due to the lack of attention for a minor character. The author's theological point of view is revealed in the characterisation of the lame man, the Jewish religious leaders, and of Jesus. Although the lame man himself is generally regarded as one of the 'minor characters' who appears in the gospel, the narrative of the lame man's healing is an important part of John's Christology and doxology, establishing Jesus as the Son whom God the Father sent to do God's work not for his own glory, but for the glory of God the Father. An analysis is undertaken of the literary traits and various characterisations evident in the seven scenes of John 5's account of the healing of the lame man, comparing him with other minor characters in John 4 and 9 who were healed. Contribution In this article a narratological and exegetical approach is employed to identify the Christological and doxological significances in John 5 by exploring the literary traits of the narrative point of view and character presentation through the theological perspective of the narrator.